Formation mechanism and implication of analcime in the sandstone reservoirs of the Permian Jingjingzigou formation in the Jinan sag, southern Junggar basin, NW China - Lin, Tong; Wang, Weiwei; Ma, Qiang; Kang, Jilun; Yang, Runze; Liu, Xiaohong (Frontiers in Earth Science, 2024)
Analcime plays a significant role in sandstone reservoirs as an authigenic diagenetic mineral in the Junggar Basin (northwestern China). However, the origin and controls on the reservoirs have received remarkably little attention. This study investigates the formation mechanism of analcime in the Middle Permian strata in the Jinan sag (southern Junggar Basin) through petrography and geochemistry. The results show that analcime is formed through early alkaline hydrolysis of volcanic materials under specific temperature and pressure conditions. The reservoir rocks primarily consist of various lithic sandstones, including volcanic debris such as basalt, andesite, and tuff. Analcime is characterized as rich in aluminium and poor in sodium, classified as low-silica analcime with a low Si-Al ratio (1.98–2.38). Furthermore, various other diagenetic minerals, such as glauconite, chlorite, albite, and calcite have been identified. The primary reservoir space chiefly consists of intragranular dissolved pores of analcime, while secondary pores are formed by intragranular pores of feldspar and lithic, along with some remaining intergranular pores. Cementation of analcime during early diagenesis changes primary pore structures and reduces reservoir properties. The low-silica analcime dissolves due to acidic pore fluids associated with three stages of oil and gas charging, transforming into albite and creating numerous secondary pores, thereby enhancing reservoir quality.